Drastic changes in acute stroke treatment. Issue 5 (21st July 2020) - Kimura, Kazumi; Nito, Chikako; Nishiyama, Yasuhiro; Suda, Satoshi; Aoki, Junya; Saito, Tomonari; Suzuki, Kentaro; Sakamoto, Yuki; Katano, Takehiro
Abstract: t‐PA therapy has been able to be performed based on RCT study results in the world from 25 years ago. However, the Japan government approved the use of t‐PA 15 years ago. In the last 15 years, diagnostic imaging and treatment for acute stroke have been changed remarkably. The appearance of diffusion‐weighted images as diagnostic imaging for acute stroke and mechanical thrombectomy as treatment for acute stroke can markedly improve patient outcome. We experienced many severe patients treated with such therapies discharged by walk. Therefore, we would like to emphasize that stoke treatment has been changed drastically. Unfortunately, at present, stroke patients who do not have benefit from t‐PA therapy and mechanical thrombectomy therapies are not so many. In order to solve those problems, we should need to establish a stroke medical care system in Japan as soon as possible. In this presentation, we will outline the image of acute stroke, acute treatment, and stroke medical care system.